A retrospective study on patients with appendicular mass after successful conservative treatment and to assess the need for interval appendicectomy - N., Sasikumar M.; Mammen, Sam Christy; Das, Shankar (International Surgery Journal, 2018)
Background: Appendicular mass is one sequelae in unoperated cases of acute appendicitis which are managed conservatively followed by interval appendicectomy (IA). Currently the need for IA has been questioned due to low risk of recurrence. Methods: Data of all AM patients from 2005 to 2010 were collected and revised the following parameters: age, sex, length of hospital stay, symptoms and signs, total leucocyte count and USG. Those who developed similar pain and those who underwent emergency appendicectomy were considered as recurrence. Patients were grouped as: 1-patients who developed RIF pain,2-asymptomatic patients,3-patients who developed recurrent a/c appendicitis,4-patients who did not developed recurrent a/c appendicitis. Results: Of the 93 patients, 12 patients underwent IA. Average duration between mass resolution and recurrence is 4.16 months. 14.8% patients had recurrent similar abdominal pain, and only 7.4% patients had recurrent acute appendicitis. Length of hospital stay had a statistically significant correlation with recurrence. The mean TC in the group with recurrent acute appendicitis was 12,500 and asymptomatic group who had a mean TC of 10678.28 which was statistically significant. Conclusions: Conservative treatment is successful for majority of appendicular masses. A routine IA seems unnecessary. Asymptomatic patients can be followed up without IA. Most of the recurrences occur within the first 3 to 6 months. Length of hospital stay and total leucocyte count influenced the recurrence. IA may be considered in those who are prone for recurrence.